Nyekar As A Religious And Cultural Tradition: An Interdisciplinary Review Of Grave Pilgrimage In The Context Of Islam In The Archipelago - Isfiana Oktaria Nasihatul Umami (International Journal of Religion and Social Community, 2024)
This article examines the tradition of nyekar, or grave pilgrimage, in the Islamic Archipelago as a religious and cultural phenomenon that has significance for Indonesian society. This paper is based on the important role of nyekar in the lives of Muslims in the archipelago, where the practice is not only seen as a form of respect for ancestors but also as a spiritual means to reflect on life after death and strengthen social relations. This tradition illustrates the fusion of Islamic teachings and local culture, making it a distinctive practice in Nusantara Islam. This research uses an interdisciplinary approach by combining theological, anthropological and sociological studies to understand the various aspects inherent in the nyekar tradition. The method used is qualitative, with data collection techniques through literature studies. The data were analysed descriptively-interpretatively to explore the meaning and importance of nyekar from various disciplinary perspectives. The research findings show that nyekar is a tradition full of religious and cultural values in which Nusantara Muslims combine religious beliefs with local customs. Besides reflecting religious practices, nyekar also serves as a means of maintaining social ties and preserving cultural identity. This article concludes that the nyekar tradition in Nusantara Islam has a dual role, namely as a form of worship and as an effort to preserve cultural values that are passed down between generations.